KONSEP FITRAH MANUSIA DALAM AL-QURAN DAN IMPLIKASINYA DALAM PENDIDIKAN ANAK USIA DINI - Muliya Rahayu (LP3M IAI Al-Qolam Malang, 2016)
God created man with a dimension of perfection that encompasses many dimensions, namely; jasadiyah that arranges everything physical aspects of the human dimension; and nafsiyah which regulates desire as well as mind and thoughts, feelings, will and freedom to live life on earth; and the dimensions of ruhiyah that has spiritual and transcendental aspects and can collaborate with dimensions of jasadiyah and nafsiyah. Early childhood education or tarbiyah al-aulÄd is an effort to optimize the childrenâ€™s potencies in accordance with the nature of the various dimensions to perfection. Dimensions of perfection is intended that when the child becomes an adult he will become the ideal inheritors of the earth. Keywords: Dimensions, fithrah, human